Assessing the Impact of Job Promotion on Employee Performance: Evidence from Deposit Banks in Indonesia - Bagus Dirgantoro; Ari Widi Prakasa; Gusti Kade Birawan (Divisi Riset, Lembaga Mitra Solusi Teknologi Informasi (L-MSTI), 2026)
This study examines the effect of job promotion on employee performance in the Indonesian banking sector. A quantitative approach was applied through questionnaires distributed to 100 employees who had received promotions within the last one to three years. Respondents were drawn from Bank Negara Indonesia (BNI), Bank Rakyat Indonesia (BRI), Bank Mandiri, and Bank Central Asia (BCA). Employee performance was evaluated through three indicators: work productivity, job satisfaction, and organizational commitment. The findings indicate that job promotion has a positive effect on employee productivity, job satisfaction, and organizational loyalty. Employees who received promotions tended to demonstrate stronger work motivation and greater organizational attachment after occupying higher positions. The study also found that employee readiness and managerial support influenced the effectiveness of promotion policies in improving work performance. Fair and transparent promotion practices were associated with higher employee morale and stronger relationships between employees and the organization. These findings may assist banking management in developing promotion systems that are more objective, measurable, and aligned with employee performance improvement.